CIVIS - A Coercion-Resistant Election System - Araujo, Roberto; Neto, André; Traoré, Jacques (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2018: Anais do XVIII Simpósio Brasileiro de Segurança da Informação e de Sistemas Computacionais, 2018)
Coercion is an intrinsic problem of Internet elections that certainly prevent its wide use. Although there is no optimal solution for this problem, modern cryptographic election schemes can mitigate it. Most of these proposals, however, were never used to carry out real elections due to the lack of software implementations. As a result, it is not possible to test these schemes in realistic election scenarios and so their interest remain purely theoretical. In this context, this work introduces the CIVIS election system. CIVIS is a web-based system that implements ideas to fight coercive attacks. It is based on a secure coercion-resistant election scheme and it shows the applicability of this scheme to accomplish realistic elections. Besides introducing CIVIS, we show that a famous Internet-based election system used in Brazil does not satisfy important security properties for voting.